Innovation in Development of Integrated Field Laboratory Faculty of Agriculture Kadiri Islamic University East Java - Titik Irawati; Nunuk Helilusiatiningsih; Edy Soenyoto (Formosa Journal of Applied Sciences, 2022)
Laboratory development has great potential in increasing innovation skills of students who were practicing cultivation, animal husbandry, fisheries, post-harvest processing, and agribusiness at the UNISKA Faculty of Agriculture, Kediri. The problem faced was that laboratory development innovation requires substantial funds in preparing facilities and infrastructure in order to increase human resources and natural resources. The research objective was to study the need for existing facilities in new innovations in the development of an integrated field laboratory. The research implementation method is the Gold method which consists of collecting data by means of descriptions, investments, analysis, concepts, designs and relevant literature studies. The research time is from May to August 2022. The results of observations and data recording are concluded as follows: The land that has been used for innovation in student practicum and research activities is 1 hectare and about 3 hectares outside the laboratory was planted with sugar cane. The laboratory has been built since 2018 and can be used for campus activities. Plant results found in the lab. Includes mango, passion fruit, watermelon, melon, tomato, brambang, turi flower, corn, mustard greens, lombok, eggplant, sere leaf, elephant grass, longan, jackfruit. There are 10 cows, 24 goats, 4 arabic chickens, 4 KUB chickens, also aquaculture, namely 50 koi fish and 300 tilapia, all on 1 hectare of land, the other 3 hectares are planted with sugar cane.